CHEMICAL COMPOSITION AND THERAPEUTIC PROPERTIES OF THE DRY EXTRACT OF PEPPERMINT (MENTHA PIPERITA) - Ibrohim Asqarov; Otakhonov Qobuljon Qakhramonovich; Mokhichexra Sobirjonov (Web of Journals Publishing, 2025)
This article presents a comprehensive analysis of the botanical characteristics, chemical composition, and therapeutic significance of the Mentha piperita (peppermint) plant. The study focuses on the preparation of aqueous and alcoholic dry extracts and the quantification of their vitamin and flavonoid content. Using the High-Performance Liquid Chromatography (HPLC) method, it was found that among the vitamins, vitamin B3 is present in the highest concentration. Among the flavonoids, salicylic acid and kaempferol were identified as dominant compounds. The study emphasizes the potential health benefits of these bioactive constituents, including their antioxidant and anti-inflammatory properties, making peppermint extract a valuable resource in phytotherapy and nutraceutical development.
Keywords: Mentha piperita, dry extract, vitamin, menthol, essential oils, phenolic compounds, rutin, gallic acid, salicylic acid, kaempferol.